Lightweight scheme selection for automotive safety structures using a quantifiable multi-objective approach. (20th December 2019) - Chu, Yantao; Sun, Lingyu; Li, Lijun
Abstract: The main objective of this paper is to propose a quantifiable multi-objective evaluation approach method to rationalize the subjective evaluation in the selection of lightweight scheme for automotive safety components, which can be applied in the selection of materials and structures in lightweight design of automobiles and other products. The proposed method combines intuitionistic fuzzy number theory, entropy method and Technique for Order Preference by Similarity to Ideal Solutions (TOPSIS) to deal with uncertainty in the decision-making process. Intuitionistic fuzzy number theory was used to quantifies the subjective evaluation of decision makers. Entropy method and fuzzy logic theory were utilized to objectively weight the criteria and decision makers, and The TOPSIS method is used to assess the pros and cons of alternatives. To assess and validate the effectiveness of the proposed method, three automotive bumper systems using different materials and structures, namely, high strength steel (HSS), polymer composite-metal hybrid (PMH), and glass fiber-reinforced aluminum laminates (GLARE) were taken as example, some qualitative criteria including recyclability and easy manufacturability as well as several quantitative criteria such as the weight, cost, crash safety (energy absorption, peak impact force and maximum deflection), were considered and balanced. According to the findings, the evaluation results of the proposed method are consistent with the evaluation results of the existing VIKOR method and TOPSIS method, which verifies the correctness of the proposed method. In addition, from the perspective of sensitivity analysis results and method principles, it is proved that the proposed method is superior to the other two methods in robustness and efficiency.